1981
DOI: 10.1159/000250264
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Ichthyosis

Abstract: In the epidermis from 4 cases of X-linked ichthyosis, granular cells contained a large number of keratohyalin granules of irregular surface, the largest ones having a spongy appearance. Keratinosomes were normal both in number and degree of extrusion. Corneal cells were linked by desmosomal discs up to the most superficial layers. The abnormal persistence of desmosomal discs may be a consequence of a decrease in the activity of acid hydrolases within the keratinosomes. In corneal cells there were a great numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…A similar finding was also observed in the U nnaT host type hereditary palm oplantar hyperkeratosis [14] and X-linked ichthyosis [19], and is thought to be related to retention hyperkeratosis. Although the reason why the horny cells in our case lack flattening is unknown, the prominent hyperkeratosis may be related to the presence of numerous desmosomal discs.…”
Section: Discussionsupporting
confidence: 82%
“…A similar finding was also observed in the U nnaT host type hereditary palm oplantar hyperkeratosis [14] and X-linked ichthyosis [19], and is thought to be related to retention hyperkeratosis. Although the reason why the horny cells in our case lack flattening is unknown, the prominent hyperkeratosis may be related to the presence of numerous desmosomal discs.…”
Section: Discussionsupporting
confidence: 82%
“…There is some evidence that there is a direct relationship between steroid sulfatase deficiency, cholesterol sulphate accumulation, and disease expression . Ultrastructural studies of RXLI show a lack of desmosomal disk disappearance (AntonLamprecht, 1974), normal LBs, and LB secretion (Mesquita-Guimarã es, 1981).…”
Section: Human Disorders Of Cornificationmentioning
confidence: 99%
“…Further, the accumulated stratum corneum in recessive X-linked ichthyosis may be caused by the inhibition of trypsin-like and chymotrypsin-like proteases by excessive CS. This could account for the abnormal persistence of numerous desmosomal structures in the outermost layers of the stratum corneum in this disease (Anton-Lamprecht, 1974;Bazex et al, 1978;Mesquita-Guimaraes, 1981). Our results suggest a possible new role of CS as an inhibitor in desquamation.…”
Section: Discussionmentioning
confidence: 53%
“…Lundström and Egelrud also reported that chymotrypsin-like enzyme activity in the stratum corneum may play a role in the desquamation process (Lundström and Egelrud, 1991;Sondell et al, 1995). It was reported that numerous desmosomal structures remained in the outermost layers of the stratum corneum in recessive X-linked ichthyosis (Anton-lamprecht, 1974;Bazex et al, 1978;Mesquita-Guimaraes, 1981). Because CS inhibited the serine protease, acrosin, required for normal sperm capacitation (Burck and Zimmerman, 1980), in this study we examined the possibility that CS acts as a protease inhibitor, retarding desquamation of stratum corneum.…”
mentioning
confidence: 99%